Membentuk Soft Skill Peserta Didik - Mori Dianto; Triyono Triyono (Jurnal Counseling Care, 2019)
This research is motivated by the phenomenon that researchers found in the field, the role of guidance and counseling teachers in shaping the soft skills of students. The phenomenon that researchers found in the field was the role of guidance and counseling teachers in shaping students' soft skills. The key informants and additional informants in this study were: BK teachers, school principals, curriculum representatives, homeroom teachers and subject teachers. in forming soft skills in terms of planning, implementation, and evaluation of service results. The results of this study are recommended for guidance and counseling teachers in order to improve the pedagogical, personality and social competencies of guidance and counseling teachers in providing services related to shaping students' soft skills.